Antimicrobial Activity of Agastache Honey and Characterization of Its Bioactive Compounds in Comparison With Important Commercial Honeys - Anand, Sushil; Deighton, Margaret; Livanos, George; Morrison, Paul D.; Pang, Edwin C. K.; Mantri, Nitin (Frontiers in Microbiology, 2019)
There is an urgent need for new effective antimicrobial agents since acquired resistance of bacteria to currently available agents is increasing. The antimicrobial activity of Mono-floral Agastache honey produced from Australian grown Agastache rugosa was compared with the activity of commercially available honeys derived from Leptospermum species and with Jarrah honey for activity against clinical and non-clinical strains of Staphylococcus aureus (methicillin-susceptible and methicillin-resistant strains), Pseudomonas aeruginosa and Escherichia coli. The minimum inhibitory concentration (MIC) for Agastache honey was in the range of 6-25% (w/v) for all species examined. The MICs for Leptospermum honeys were generally similar to those of Agastache honey, but MICs were higher for Super manuka and Jarrah honeys and lower for Tea tree honey. Staphylococci were more susceptible to all honeys than Pseudomonas aeruginosa and Escherichia coli. Pretreatment of honey with catalase increased the bacterial growth at MIC of Tea tree honey (35%), Super Manuka (15%), Jarrah honeys (12%) and Agastache honey (10%), indicating variable contributions of hydrogen peroxide to antimicrobial activity. Manuka and Jelly bush honeys retained their antimicrobial activity in the presence of catalase, indicating the presence of other antimicrobial compounds in the honey. An LC-MS/MS method was developed and used to identify possible antimicrobial phenolic compounds in Agastache honey and flowers, and five commercial honeys. The chemical markers characteristic of Agastache honey and honeys of Leptospermum origin were phenyllactic acid and methyl syringate. Overall, the bioactive compounds with antimicrobial and antioxidant activity in Agastache honey suggested a possible use for topical application and in wound care.